Flexible Pressure Sensor Based on a Poly(VDF‐TrFE) Nanofiber Web. Issue 5 (17th December 2012) - Ren, Guangyi; Cai, Fanyi; Li, Baozhang; Zheng, Jianming; Xu, Chunye; Kim, Il‐Doo
Abstract During electrospinning, P(VDF‐TrFE), an electroactive polymer, acquires special electrical and mechanical properties. The development of a flexible, breathable pressure sensor based on P(VDF‐TrFE) nanofiber webs is reported that shows promise for use in human‐centered applications. The P(VDF‐TrFE) nanofiber webs are produced by electrospinning. The morphology and microstructure of webs are characterized using SEM, XRD, and ATR‐FTIR spectroscopy. Flexible pressure sensors are developed that are suitable for incorporation into fabrics and, using a custom‐made setup, is is demonstrated that they have a maximum sensitivity of 60.5 mV · N−1. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>